Prenatal Diagnosis of Coronary Artery Fistula: A Case Report and Review of Literature - Mohamed Nagiub; Deemah Mahadin; Srinath Gowda; Sanjeev Aggarwal (Thieme Medical Publishers, Inc., 2014)
Abstract We report an antenatally diagnosed large distal coronary artery fistula (CAF) arising from an aneurysmal dilation right coronary artery (RCA) and draining in to the right ventricle (RV) just below the septal leaflet of tricuspid valve posteriorly. A postnatal echocardiogram confirmed the diagnosis. On the second day of life, a percutaneous partial closure of the fistula was performed by placing a Flipper coil (Cook Medical, Bloomington, IN) in the RCA just proximal to the drainage site in the cardiac catheterization laboratory. Follow-up echocardiogram on the day following the procedure showed improved forward flow in the descending aorta with decreased RV size. Our case report suggests that antenatal diagnosis of a CAF may aid in early intervention. Partial closure of the fistula in the cardiac catheterization laboratory is safe and effective.